Penurunan Kadar pH dengan Metode Filtrasi menggunakan Media Pasir dan Tanah Liat pada Water Treatment Plant Pusat Pengembangan Sumber Daya Manusia (PPSDM MIGAS) Cepu - Miftakhul, Khoiriah; Stighfarrinata, Rizky (Universitas Bojonegoro, 2023)
Water is essential for development and growth, benefiting both humans and other living organisms. Clean water scarcity is a common issue, leading to a crisis as demand grows. Polluted water consumption can cause health problems like diarrhea, cholera, polio, and poisoning. Diarrhea, often linked to water pollution, can lead to dehydration and death, especially in children, while poisoning can cause anemia, hypertension, and nervous system issues. To address this, effective water treatment is necessary, and filtration is an affordable, accessible option. While activated carbon is commonly used, it is expensive. This study shows that sand and clay are effective for treating contaminated water, achieving 95% pH normalization and meeting the required standards.